Regen med therapeutic opportunities for fighting COVID‐19. (27th August 2020) - Atala, Anthony; Henn, Alicia; Lundberg, Martha; Ahsan, Taby; Greenberg, Jordan; Krukin, Jeff; Lynum, Steven; Lutz, Cat; Cetrulo, Kyle; Albanna, Mohammad; Pereira, Taciana; Eaker, Shannon; et al.
Abstract: This perspective from a Regenerative Medicine Manufacturing Society working group highlights regenerative medicine therapeutic opportunities for fighting COVID‐19. This article addresses why SARS‐CoV‐2 is so different from other viruses and how regenerative medicine is poised to deliver new therapeutic opportunities to battle COVID‐19. We describe animal models that depict the mechanism of action for COVID‐19 and that may help identify new treatments. Additionally, organoid platforms that can recapitulate some of the physiological properties of human organ systems, such as the lungs and the heart, are discussed as potential platforms that may prove useful in rapidly screening new drugs and identifying at‐risk patients. This article critically evaluates some of the promising regenerative medicine‐based therapies for treating COVID‐19 and presents some of the collective technologies and resources that the scientific community currently has available to confront this pandemic.